An ARDL investigation on the nexus of oil factors and economic growth: A timeseries evidence from Sultanate of Oman - Sarfaraz Javed; Uvesh Husain (Cogent Economics & Finance, 2020)
The study is conducted to comprehend the relation of the oil sector with Oman's economic growth. Oman is an abundant oil country, and the oil sector plays an influential part in its economic development. The data were gathered from a range of 1989 to 2018 from the National Center for Statistics and Information of Oman; it published the statistical year for variables including oil revenue, oil price, gross capital formation, total revenue, and production or export of Crude Oil. The data were analyzed with the help of the ARDL cointegration approach and Granger causality test. The results enlighten that economic performance is significantly affected by the oil price, crude oil production, and gross capital formation, and the total revenue and oil revenue insignificantly influence it. The impact of export has a substantial adverse influence on economic growth. The variables have long-run granger cause on each other while short-run causal bidirectional relation exists among economic performance, crude oil production, and export of Crude Oil. The study helps Oman's Government understand the importance of the oil sector and aids in maintaining or forecasting the oil revenue and government spending to retain a stable economy.
Keywords: 330; ARDL estimation; economic growth; oil revenue; Oman